2019
DOI: 10.1097/pec.0000000000001923
|View full text |Cite
|
Sign up to set email alerts
|

A Pulse Check on Leadership and Teamwork

Abstract: Objectives: Effective leadership and teamwork are imperative during pediatric cardiopulmonary resuscitations (CPR). The initial phase of pediatric CPR, termed the "first 5 minutes," has significant care delivery gaps in both leadership and team performance. The aim of the study was to describe the performance data of emergency department (ED) teams who performed CPR in a pediatric ED. Methods:We conducted a retrospective video review of resuscitations involving pediatric patients younger than 21 years who pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…It is well demonstrated that inefective communication and teamwork directly compromise patient care, lead to staf distress, and are a contributory factor in the majority of hospital sentinel events [18,[22][23][24][25][26]. In fact, teamwork and leadership have been found to be so integral to cardiopulmonary resuscitation that they have been included in guidelines for advanced life support [10,27]. In a pre-/postimplementation study assessing the utility of a PICU daily patient goal sheet, the use of the protocol improved both physicians' and nurses' perceived understanding of patient care goals as well as nurses' ability to accurately identify a patient's physician team [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that inefective communication and teamwork directly compromise patient care, lead to staf distress, and are a contributory factor in the majority of hospital sentinel events [18,[22][23][24][25][26]. In fact, teamwork and leadership have been found to be so integral to cardiopulmonary resuscitation that they have been included in guidelines for advanced life support [10,27]. In a pre-/postimplementation study assessing the utility of a PICU daily patient goal sheet, the use of the protocol improved both physicians' and nurses' perceived understanding of patient care goals as well as nurses' ability to accurately identify a patient's physician team [7].…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, conflict, confusion, and miscommunication are all too common. Examples of these situations include code blue teams and day-to-day rounding teams, in contrast to situations in which roles are well defined such as operating room teams [25][26][27][28].…”
Section: The Structure Of Teams In Health Carementioning
confidence: 99%